Improving Financial Management via Contemplation: Novel Interventions and Findings in Laboratory and Applied Settings - Harkin, Ben (Frontiers in Psychology, 2017)
The present research tackles two main areas of financial mismanagement, namely avoiding debt-related information and underestimating expenditure. We draw upon research which has shown that inviting people to think about reasons for avoiding something actually serves to reduce the likelihood that they will then avoid it, and potentially improves what they know about it. Therefore, in three studies we investigated if prompting participants to contemplate their debt (Studies 1 & 2) and expenditure (Study 3) would decrease avoidance of debt-related information and improve estimates of expenditure, respectively. Conform to our expectations prompting contemplation via questionnaire (Study 1) and video (Study 2) reduced avoidance of debt-related information. In other words, contemplation reduced the likelihood that people would avoid viewing their risk of debt. The success of prompting contemplation via video offers a new and important addition to the literature on contemplation, which has previously focused on using the traditional questionnaire format. In Study 3 we observed that contemplation improved the estimates of expenditure that loan applicants at a credit union provided. Specifically, contemplation resulted in participants providing larger and more detailed accounts of their expenditure, and increased the agreement between staff and clients for the number of expenditure items provided by the clients. In sum, these findings suggest that contemplation in the context of the above financial decision-making is a robust intervention, as it was effective for different types of interventions (questionnaire and video), behaviours (avoidance of debt-related information and improving estimates of expenditure), and samples (students and university staff; Studies 1 & 2 and loan applicants at a credit union; Study 3). We discuss the theoretical, policy and applied impact of these findings, and highlight limitations and considerations for future research.